Comparing Male and Female Engineering Students' Reading Ability through Level-Specific Tasks and CEFR- and DIALANG-Based Self-Assessment - Mahboubeh Taghizadeh; Farshad Kazemzadeh (Comparative Education Society of Iran ( CESIR), 2019)
The purposes of this study were to determine a reading ability level based on the CEFR for male and female engineering students and to compare their reading levels on the CEFR and DIALANG self-assessment grids with the level based on their performance on the reading tasks. The participants were 162 Iranian male and female undergraduate students at the Iran University of Science and Technology. DIALANG and CEFR reading self-assessment grids and four reading tasks at four levels (i.e., A2, B1, B2, and C1) were administered to the participants. Considering the students' performance on the reading tasks, the results revealed that female learners outperformed the male learners; however, a considerable number of learners (about 40%) in both groups were considered 'Below B1'. The results also showed that learners' self-assessment did not closely correspond with their performance on the reading tasks as both groups of learners rated their reading ability lower on the CEFR and DIALANG grids; nevertheless, the highest matches were related to the female learners' ratings on the DIALANG grid.